2008
DOI: 10.1158/1078-0432.ccr-08-0702
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Lymphoid Tissue Lymphoma: Novel Translocations Including Rearrangements of ODZ2, JMJD2C, and CNN3

Abstract: Purpose: The well-known translocations identified in MALT lymphomas include t(11;18)/API2-MALT1, t(1;14)/IGH-BCL10, and t(14;18)/IGH-MALT1. Molecular investigations have suggested that these three disparate translocations affect a common pathway, resulting in the constitutive activation of nuclear factor-nB. However, the vast majority of MALT lymphomas are negative for any of the above-mentioned translocations and the underlying pathogenesis is unclear. Experimental Design: Fresh tissue of 29 gastric and extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 29 publications
(30 reference statements)
2
63
1
Order By: Relevance
“…These include t(1;14)(p21;q32), t(5;14)(q34;q32), t(9;14)(p24;q32) and t(3;14)(p13;q32), which result in placement of the CNN3, ODZ2, JMJD2C and FOXP1 genes, respectively, downstream of the IGH promoter element. [29][30][31] Detailed information regarding the many genetic abnormalities associated with MALT lymphoma has been provided in a recent review in reference 32.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…These include t(1;14)(p21;q32), t(5;14)(q34;q32), t(9;14)(p24;q32) and t(3;14)(p13;q32), which result in placement of the CNN3, ODZ2, JMJD2C and FOXP1 genes, respectively, downstream of the IGH promoter element. [29][30][31] Detailed information regarding the many genetic abnormalities associated with MALT lymphoma has been provided in a recent review in reference 32.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…[128][129][130][131]142,143 More recently, three novel IgH translocations in non-gastric MZBCL involving ODZ2, CNN3 and JMJD2C have been described, of which ODZ2 and JMJD2C were found recurrently. 144 The t(11;18) is present in ~40% of pulmonary-and iñ 20% of gastric-MZBCLs and is virtually absent in MZBCLs of the salivary gland (Table 2). 86,[128][129][130][131][132][133][134] Gastric MZBCLs harboring the t(11;18) were found to be associated with CagA-positive strains of H. pylori.…”
Section: Genetic Alterations In Low-and High-grade Extranodal Marginamentioning
confidence: 99%
“…26,46,47 We did not detect any new or recently described sporadic translocations, such as t(6;7)(q25;q11), 48 t(X;14)(p11.4;q32), 49 and translocations involving chromosomal regions on chromosome arms 1p, 1q, 5q and 9p. 48 No loss or amplification of any of the studied regions was seen.…”
Section: Discussionmentioning
confidence: 89%
“…26,46,47 We did not detect any new or recently described sporadic translocations, such as t(6;7)(q25;q11), 48 t(X;14)(p11.4;q32), 49 and translocations involving chromosomal regions on chromosome arms 1p, 1q, 5q and 9p. 48 No loss or amplification of any of the studied regions was seen.Similarly to other studies we found that trisomies 3 and 18 were the most common numerical aberrations in extranodal marginal zone lymphoma, 14,17,24,27,31,32,35,50,51 and extranodal diffuse Table 1 Clinicopathological and FISH data of extranodal marginal zone lymphoma and diffuse large B-cell lymphoma of the thyroid, testis and breast for detection of t(11;18)(q21;q21) (t(1;14)(p22;q32), t(14;18)(q32;q21) involving IGH/MALT1 and IGH/BCL-2 and numerical aberrations of chromosomes 1, 3, 12 and 18 …”
mentioning
confidence: 89%